2016
DOI: 10.1016/j.jcma.2016.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Development of the ultrasonography learning model for undergraduate medical students: A case study of the Faculty of Medicine, Burapha University

Abstract: By adding hands-on ultrasound experience using live patients proctored by radiologists for final year medical students, in the space of 2 weeks, an effective ultrasound learning model for undergraduate medical students can be provided. This model should be considered in the curricular design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
9
0
2
Order By: Relevance
“…120,121,124,128 Eight studies compared dedicated electives or boot-camps to standard training. 57,65,68,104,129,130,132 Five of these revealed better outcomes with electives. 68,104,129,130,132 In two separate studies, Jang et al 129,130 found that elective groups performed a threshold number of scans in a significantly shorter time frame, and had equivalent image acquisition and interpretation scores compared to standard training.…”
Section: Electives/boot-campsmentioning
confidence: 97%
See 2 more Smart Citations
“…120,121,124,128 Eight studies compared dedicated electives or boot-camps to standard training. 57,65,68,104,129,130,132 Five of these revealed better outcomes with electives. 68,104,129,130,132 In two separate studies, Jang et al 129,130 found that elective groups performed a threshold number of scans in a significantly shorter time frame, and had equivalent image acquisition and interpretation scores compared to standard training.…”
Section: Electives/boot-campsmentioning
confidence: 97%
“…57,65,68,104,129,130,132 Five of these revealed better outcomes with electives. 68,104,129,130,132 In two separate studies, Jang et al 129,130 found that elective groups performed a threshold number of scans in a significantly shorter time frame, and had equivalent image acquisition and interpretation scores compared to standard training. Maskatia et al 68 found that fellows trained in an intensive three-day "boot-camp" had superior image acquisition and interpretation scores than historical cohorts trained over a longer time.…”
Section: Electives/boot-campsmentioning
confidence: 97%
See 1 more Smart Citation
“…We have been reported the effectiveness of a dedicated 2-week radiology rotation on the US image interpretation skill elsewhere. [ 11 ] In that study, the students who got better scores chose radiology rotation as an elective rotation, and selection bias was questioned. The present study confirms that either interested or noninterested students could get better scores if they received dedicated teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our previous study has shown that US experience has no impact on the US test score. [ 11 ] Our program offered to students are intended for interactive sessions, and thus, the number of students per rotation was limited. This type of education may not be established in some institutions where the radiologists are a shortage or have a greater number of students.…”
Section: Discussionmentioning
confidence: 99%